Psychological Distress of Female Young Adults Who Experienced Infidelity In Dating Relationships - Felia Syifa Budyningrum; Atika Dian Ariana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Infidelity is a deeply personal and emotionally devastating experience, particularly for young adults navigating the complexities of romantic relationships. This study examines the psychological distress of Indonesian female young adults (aged 18-29) who experienced infidelity in dating relationships. Using a qualitative, instrumental case study approach, it explores their emotional, cognitive, and relational struggles. Findings reveal significant distress, including anxiety, depressions, and emotional dysregulation, and trust issues, impacting their self-esteem and relationships. Coping mechanisms ranged from supportive relationships and therapy to maladaptive behaviors like self-harm. This study underscores the need for mental health interventions tailored to this group and calls for future research on cross-cultural perspectives and long-term recovery.